How Transactional Leadership Style and Work Environment Influence Gen Y Job Satisfaction in PT XYZ thus Impact to the Employee Loyalty - Tinjung Desy Nursanti; Amanda Lesmana; Viska Yuliana (Indonesia Banking School, 2020)
The purpose of this study is to analyze what and how the influence of transactional leadership style, work environment on job satisfaction has an impact on the loyalty of Generation Y employees who work in the company. Employees themselves are important assets of the company in achieving company goals, there-fore this is an important thing for the company to understand. The research method used in this study used an associative design by distributing questionnaires to Generation Y employees at PT. XYZ and analyzed using Path Analysis. From the results of this analysis, it can later be used as consideration and reference for the company for taking the next step in order to increase the satisfaction of Generation Y employees and to overcome and avoid problems related to the loyalty of Generation Y employees in the company in the fu-ture. For example, by showing concern or paying special attention to Generation Z employees, in order to build a positive attitude towards work and working conditions. It is hoped that these things can increase job satisfaction which has an impact on increasing their loyalty.